Efficiency Evaluation of Construction of Steam-Turbine Power Plants at Industrial Enterprises - A. L. Starzhinsky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
It is shown that application of own power stations at an industrial enterprise is considered as an expedient one if there is an availability of thermal power sources because value of an optimization criterion exceeds corresponding optimization criterion by 2.1-4.6 fold when an enterprise is supplied with power only from power system networks.